Prevention of Early Marriage in Building a Problem Family - Khurul Anam (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to explore and analyze strategies for preventing early marriage in the context of building a maslahah family. The research method used is a qualitative approach with descriptive analysis techniques. Data was collected through literature reviews and case findings in the field related to the research topic. Data analysis was carried out systematically, by presenting and interpreting the main findings that emerged from the process. The results of this research reveal the complexity of factors that influence the practice of early marriage, including social, cultural, economic and religious factors. The findings show variations in views and experiences among respondents regarding the prevention of early marriage. Descriptive analysis also identifies patterns in prevention strategies that have been implemented by various parties, from families, communities, to social and religious institutions. The implication of this research is a deeper understanding of the issue of preventing early marriage in the context of building a quality family. These findings can provide a basis for the development of policies, intervention programs and community strategies that are more effective in addressing the problem of early marriage. In addition, this research also makes an important contribution to academic and practical understanding of the social and cultural dynamics that influence family formation in society. Thus, this research emphasizes the importance of a qualitative approach with descriptive analysis techniques as an effective tool in understanding and overcoming the challenges faced by society regarding the issue of preventing early marriage.